Why the coalition of political party are weak in election of regional head (Legal and Political Perspective) - Ropii, Imam; Soleh, Mukhammad (Technium Social Sciences Journal, 2023)
This article examines why coalitions of political parties for regional head elections are weak. The law on regional head elections requires political parties to nominate a regional head/deputy pair that must have the support of at least 20% of the total members of the regional people’s representative council. Political parties not meeting the amount of support must form a coalition with other parties to meet these requirements. The results showed that the coalition of political parties in the regional head election was weak due to: a) Strong centralization of political parties in determining coalition partners. b) Strong dominance of the party’s central board. c) High political costs for regional head elections. d) Weak rights of regional political party administrators.